2018
DOI: 10.1007/s00464-018-6090-7
|View full text |Cite
|
Sign up to set email alerts
|

Force-based learning curve tracking in fundamental laparoscopic skills training

Abstract: BackgroundWithin minimally invasive surgery (MIS), structural implementation of courses and structured assessment of skills are challenged by availability of trainers, time, and money. We aimed to establish and validate an objective measurement tool for preclinical skills acquisition in a basic laparoscopic at-home training program.MethodsA mobile laparoscopic simulator was equipped with a state-of-the-art force, motion, and time tracking system (ForceSense, MediShield B.V., Delft, the Netherlands). These perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 29 publications
1
45
2
Order By: Relevance
“…However, a power analysis suggests that, respectively, 90, 27 and 27 participants are needed to show significant differences (i.e., Power of 1-beta = 0.8) between the Task time, Fz max and Fft Max parameters of the pre-and post-training group. Differently from previous learning effect studies on interaction force-related parameters [40,41], we found a clear indication that the force levels are naturally decreasing during training without the use of force feedback. Tracking the learning curves of the used force and torque parameters should give insight on how subjects shift their focus on task time (i.e.…”
Section: Limitationscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, a power analysis suggests that, respectively, 90, 27 and 27 participants are needed to show significant differences (i.e., Power of 1-beta = 0.8) between the Task time, Fz max and Fft Max parameters of the pre-and post-training group. Differently from previous learning effect studies on interaction force-related parameters [40,41], we found a clear indication that the force levels are naturally decreasing during training without the use of force feedback. Tracking the learning curves of the used force and torque parameters should give insight on how subjects shift their focus on task time (i.e.…”
Section: Limitationscontrasting
confidence: 99%
“…Within our pilot study, a reduction in task time is not observed, and the average task time in the novice post measurements even seem to increase. In contrast to this, the natural gradient of force parameter learning curves is more of a straight line without specific force-feedback and, therefore, indicates a limited decrease of tissue manipulation skills [40,41]. However, the averaged force parameters outcomes in this study do show a significant decrease in force parameters between pre-and post-course assessment.…”
Section: Portal Force and Torquecontrasting
confidence: 83%
“…Technically these advanced objective assessments can be done by sensor equipped box trainer, such as the ForceSense system (Medishield) or VR Trainer, such as the LapSim (Surgical Science) [12, 13]. However, the AGE TC clearly favor the sensor equipped box trainer over VR trainer.…”
Section: Discussionmentioning
confidence: 99%
“…Hand force/torque estimation is essential for translating human intention into control commands to external devices for various applications including human-machine interaction (Merletti et al, 2004 ; Haddadin et al, 2008 ; Pervez and Ryu, 2008 ), laparoscopic surgery training (Hardon et al, 2018 ), prosthetic control (Nielsen et al, 2010 ), tele-operation (Khurshid et al, 2016 ) and tele-assessments of home-based rehabilitation (Zhang et al, 2016 ). For human-robot interaction, it is crucial for a machine to detect an unexpected increase of contact force when the operator tries to push the machine away to protect herself/himself from injury in any hazardous situations (Haddadin et al, 2008 ; Pervez and Ryu, 2008 ).…”
Section: Introductionmentioning
confidence: 99%